2020
DOI: 10.1038/s42003-020-0983-4
|View full text |Cite
|
Sign up to set email alerts
|

SRPK1 acetylation modulates alternative splicing to regulate cisplatin resistance in breast cancer cells

Abstract: Cisplatin and other platinum-based compounds are frequently used to treat breast cancer, but their utility is severely compromised by drug resistance. Many genes dictating drug responsiveness are subject to pre-mRNA alternative splicing which is regulated by key kinases such as the serine-arginine protein kinase 1 (SRPK1). However, its contribution to drug resistance remains controversial. In this study, we have identified that Tip60-mediated acetylation of SRPK1 is closely associated with chemotherapy sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 69 publications
2
22
1
10
Order By: Relevance
“…More recently, it has been shown that PT also induced the acetylation of the serine‐arginine protein kinase 1 (SRPK1). SRPK1 acetylation was associated with its cytoplasmic localization and PT sensitivity 67 . Conversely, in PT‐resistant breast cancer cells, PT treatment reduced SRPK1 acetylation favoring the expression of antiapoptotic splicing variants of several genes 67 .…”
Section: Alternative Splicing and The Response To Platinummentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it has been shown that PT also induced the acetylation of the serine‐arginine protein kinase 1 (SRPK1). SRPK1 acetylation was associated with its cytoplasmic localization and PT sensitivity 67 . Conversely, in PT‐resistant breast cancer cells, PT treatment reduced SRPK1 acetylation favoring the expression of antiapoptotic splicing variants of several genes 67 .…”
Section: Alternative Splicing and The Response To Platinummentioning
confidence: 99%
“…SRPK1 acetylation was associated with its cytoplasmic localization and PT sensitivity. 67 Conversely, in PT-resistant breast cancer cells, PT treatment reduced SRPK1 acetylation favoring the expression of antiapoptotic splicing variants of several genes. 67 These evidences are in good accord with the general knowledge that HDACs interact with the spliceosome and participate in the control of the acetylation states of splicing factors.…”
Section: Platinum Affects the Alternative Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a decrease in the kinase activity of SRPK1, changes in the stability of this protein and, therefore, changes in its ability to regulate alternative splicing. This increase in the acetylation of SRPK1 is accompanied by an increase in the sensitivity of breast cancers to cisplatin [ 49 ]. Doxorubicin is a widely used chemotherapeutic agent for the treatment of breast cancer.…”
Section: Mirna and Alternative Splicing-induced Drug Resistancementioning
confidence: 99%
“…The targeting of the splicing process of myeloid cell leukemia-1 along with other apoptotic regulators is a new therapeutic target in breast cancer cells and provides an effective way to overcome therapy resistance in these cells [ 69 ]. Tip60-mediated acetylation of serine-arginine protein kinase 1 is closely associated with chemotherapy sensitivity [ 70 ]. In breast cancer cells, Cisplatin induces this acetylation pattern while in the corresponding resistant cells, it reduces acetylation.…”
Section: Breast Cancermentioning
confidence: 99%